Picture-based insurance: delivering affordable crop insurance using farmers' smartphone pictures to assess crop damage - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Picture-based insurance was adopted by several insurance institutions and programs: HDFC ERGO General Insurance (India), Dvara E-Registry (India), Mahalanobis National Crop Forecast Center (India), Agriculture and Climate Risk Enterprise (ACRE) Africa (Kenya), R4 Rural Resilience Initiative (Ethiopia), Centre for Agriculture and Bioscience International (India and Kenya).